2021
DOI: 10.3390/app11177802
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Coatings: EIS and SEM Applied to Evaluate the Corrosion Behavior of Steel in Fire Extinguishing Solution

Abstract: Phosphate coatings are one of the most important methods in preventing metal corrosion, especially iron alloys. The high interest in this method for industrial applications is mainly due to the low costs associated with the phosphating solution component and technological process. Considering this aspect and the advantages offered to the materials (corrosion resistance, good adhesion, wear resistance), this study evaluates the potential of using the phosphate coating method in health and safety applications. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…In the case of the painted sample, the increase in the corrosion rate could be explained by the deterioration of the paint layer. These results are expected since, when the C45 sample surface was studied by Energy Dispersive X-Ray Analysis after immersion in FES, a layer with compounds reach in oxygen from the corrosive media (FES) mixed with small quantities of corrosion products was formed [16].…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…In the case of the painted sample, the increase in the corrosion rate could be explained by the deterioration of the paint layer. These results are expected since, when the C45 sample surface was studied by Energy Dispersive X-Ray Analysis after immersion in FES, a layer with compounds reach in oxygen from the corrosive media (FES) mixed with small quantities of corrosion products was formed [16].…”
mentioning
confidence: 59%
“…Although previous studies [14][15][16] have shown that the corrosion resistance, in various corrosive environments, of the carbon steel carabiners has been significantly improved by the deposition of phosphate layers and other subsequent layers. However, knowing that the carabiners or other components of the safety systems contain pieces made of different metals, and the fact that the contact zone between these different metals will act as a galvanic couple when exposed to corrosive media, for a complete evaluation, it is also essential to analyse the galvanic corrosion of the couples which can appear between the metals used in safety systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better data modelling was achieved by replacing the capacity of the double layer (Cdl) with a constant phase element, respectively CPE (CPE-Constant Phase Element), which expresses the nonideal behaviour of capacities (capacity variation by frequency). The impedance of a constant phase element can be expressed by the relation proposed by Zoltowski [32,33] (1):…”
Section: The Cast Iron Surface Layer Structure and Composition After ...mentioning
confidence: 99%
“…Due to the importance of the cast iron in the pumping system as a material for rotors manufacturing and also for its properties, we consider that it is important to improve the corrosion resistance of the material using advanced coatings like conversion coatings [33], which can improve not only the corrosion behaviour but also the wear resistance.…”
mentioning
confidence: 99%